Entertainment computing and serious games : first IFIP TC 14 Joint International Conference, ICEC-JCSG 2019, Arequipa, Peru, November 11-15, 2019, Proceedings /: first IFIP TC 14 Joint International Conference, ICEC-JCSG 2019, Arequipa, Peru, November 11-15, 2019, Proceedings. (2019) - Unknown
No abstract available